2013
DOI: 10.4314/agrosh.v12i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Seed Beetle (<i>Callosobruchus maculatus</i>) Population with Root Bark Powder of <i>Zanthoxylum Zanthoxyloides</i> (Lam.) Waterm. (Rutaceae) on Cowpea (<i>Vigna unguiculata</i> (L.) Walp

Abstract: In view of the recently increased interest in developing botanical pesticides as an alternative to synthetic pesticides, this investigation was carried out to examine the insecticidal potentials of the Zanthoxylum Zanthoxyloides (Lam.) Waterm. (Rutaceae) Root Bark Powder against Seed Beetle, Callosobruchus 0 maculatus (F.). The experiment was carried out at ambient temperature of 28±3 C and relative humidity of 68±3% in the laboratory. Population suppression activities of Z. zanthoxyloides Root Bark Powder aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The results of this study agree with the findings of Idoko and Adesina (2012) who reported that P. guineense caused the mortality of C. maculatus adults and eventual suppression of progeny emergence due to contact toxicity of the powder. Previous investigation showed that mortality of C. maculatus increased with increase in the rate of plant part powder applied with higher rate assumed to be having higher active ingredients against the insect (Musa, 2012). The adult mortality recorded might be attributed to the leaf powders that may have caused abrasion of the insect cuticle.…”
Section: Discussionmentioning
confidence: 94%
“…The results of this study agree with the findings of Idoko and Adesina (2012) who reported that P. guineense caused the mortality of C. maculatus adults and eventual suppression of progeny emergence due to contact toxicity of the powder. Previous investigation showed that mortality of C. maculatus increased with increase in the rate of plant part powder applied with higher rate assumed to be having higher active ingredients against the insect (Musa, 2012). The adult mortality recorded might be attributed to the leaf powders that may have caused abrasion of the insect cuticle.…”
Section: Discussionmentioning
confidence: 94%
“…It can however also infest several other types of stored legume grains such as chickpea, bambara nut, mung bean, groundnut and soybean (Ekeh et al, 2013) to varying degrees. When C. maculatus attacks stored legume seeds, they deface them with eggs and holes and invariably cause a reduction in their market and nutritional value (Musa, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Insect pests constitute the most visible and important constraint to cowpea production, infesting mature pods and accounting for post-harvest reduction of grains (Musa, 2012). Cowpea is infested by bean beetle, Callosobruchus maculatus (F.) between harvest and storage leading to quantitative and qualitative losses of grains.…”
Section: Introductionmentioning
confidence: 99%